Kajian Viktimologi Terhadap Anak Korban Kekerasan Seksual di Lingkungan Keluarga - Shalahuddin Al Ayyubi; Dian Esti Pratiwi (PLEDOI (Jurnal Hukum dan Keadilan), 2023)
Cases of sexual violence against children are rife in Indonesia, especially sexual violence experienced by a child in his own family environment. Law in Indonesia has accommodated the protection of child victims of sexual violence in the family environment in Law Number 12 of 2022 concerning Crimes of Sexual Violence and Law Number 35 of 2014 concerning amendments to Law Number 23 of 2002 concerning Child Protection. Victims' rights are also regulated in other regulations, namely in Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims. In its implementation, the rule of law still has many shortcomings so that it is not optimal in solving the problems of child victims of sexual violence in the family environment. The research method used is normative by examining existing legal regulations relating to sexual violence against children. Opportunities to strengthen these articles can be accommodated in the Draft Criminal Code, so that in the future the problem of sexual violence against children in the family environment can provide the best solution.